Design and fabrication of flexible FSS polarizer. Issue 1 (18th October 2019) - Sivasamy, Ramprabhu; Kanagasabai, Malathi
Abstract: A low profile flexible linear to circular polarizer made of paper substrate is proposed in this paper. The polarizer is constructed from frequency selective surface (FSS) comprising of crossed dipole unit cell elements. The polarizer converts the linearly polarized incident electromagnetic wave to circular polarized wave at 7.0 GHz. The polarizer provides the advantage of use in conformal system, which is substantiated using bending analysis. The proposed reflective polarizer provides a 3 dB axial ratio bandwidth of 13% at the center frequency of 7.0 GHz. In addition, the proposed flexible polarizer provides stable response for angular incidences up to 30°. Prototype of the flexible FSS polarizer is fabricated and its simulation results are validated with experimental measurements.